MOTIVASI PENYUSUNAN LAPORAN KEUANGAN UMKM SERTA PROSPEK IMPLEMENTASI SAK ETAP - Sasi Syifaurohmi, 12.05.52.0206; Aini, Nur (Students Journal of Accounting and Banking, 2016)
This study aims to examine the motivation of SMEs in the financial statements as well as the prospects of implementation of SAK ETAP in Semarang. The population in this study are all SMEs in the city of Semarang. The sample in this study are randomly selected SMEs using Convenience sampling method and sample size of 100 respondents. The method of collecting primary data used is the questionnaire results showed tha, education background, size of business, information provision and dissemination of positive effect on the motivation of financial statements of SMEs while education and long effort has no effect on the motivation of financial statements of SMEs and education, educational background, size of business, providing information and socialization affect the implementation of SAK ETAP long while efforts had no effect on the implementation of SAK ETAP.Keywords:Â Levels of Education, Education Background, Size of Business, Old Business, Information Provision and Socialization, Motivation, The Implementation of SAK ETAP